Bai ‘Al-Tawarruq : concept of islamic financing? / Luqman Nurhisam - Nurhisam, Luqman (Universiti Teknologi Mara Selangor, 2016)
Shariah Committee in Malaysia in his fatwa has legitimized the execution of the contract al-Tawarruq and al-'Īnah in Islamic banking practices, while the contract is not ratified by the National Sharia Council in Indonesia. This study will discuss the reasons and background differences fatwa, and an aspect ratio of banking products and the legal framework used to legitimize Islamic financial products in Indonesia and Malaysia. Therefore, further research is needed to analyze how the views of the scholars against al-Tawarruq along with proof of his, and the extent to which the contract tawarruq has been applied in Islamic finance, especially in Indonesia and Malaysia. As a result of a comparison of Islamic financial products in general, and the legal framework used by the Sharia Board between Indonesia and Malaysia. The method used is descriptive qualitative analysis. In this study, the research subjects are the scholars of Sharia Council. While the object of research is the view of the scholars of fiqh against al-Tawarruq, aspects of financial products, and the framework of Islamic law. From this study, it was found that the mechanism of al-Tawarruq, can not be regarded as an Islamic financial products, because a lot of flaws in it. Hilah known that there are not good that lead to usury, so this is the reason of the majority of scholars do not technically separated in Indonesia. However, as far as the development of the contract used that al-Tawarruq al-fiqhi been applied in syariah commodity trading in the Jakarta Futures Exchange. While Malaysia believes that the buying and selling of al-Tawarruq is halal as the basic rule for the legitimacy of the agreement, which has been applied in private financing in Islamic banks, as well as a commodity murabaha on Bursa Malaysia namely Bursa Suq Al-Sila.